Analysis of Geophysical Networks Derived From Multiscale Digital Elevation Models: A Morphological Approach - Tay, L.T.; Sagar, B.S.D.; Chuah, H.K. (2005)
We provide a simple and elegant framework based on morphological transformations to generate multiscale digital elevation models (DEMs) and to extract topologically significant multiscale geophysical networks. These terrain features at multiple scales are collectively useful in deriving scaling laws, which exhibit several significant terrain characteristics. We present results derived from a part of Cameron Highlands DEM.